2014
DOI: 10.1155/2014/392324
|View full text |Cite
|
Sign up to set email alerts
|

Memory‐Enhancing Effects of the Crude Extract of Polygala tenuifolia on Aged Mice

Abstract: Learning and memory disorders arise from distinct age-associated processes, and aging animals are often used as a model of memory impairment. The root of Polygala tenuifolia has been commonly used in some Asian countries as memory enhancer and its memory improvement has been reported in various animal models. However, there is less research to verify its effect on memory functions in aged animals. Herein, the memory-enhancing effects of the crude extract of Polygala tenuifolia (EPT) on normal aged mice were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…("Yuanzhi" in Chinese) is a well-known traditional Chinese medicine (TCM) herb, which was first documented in Shen Nong Ben Cao Jing, and its dried root has for a long time been traditionally used to treat memory loss in Asian countries (Howes and Houghton, 2003;Kwon et al, 2004;Adams et al, 2007). Recent pharmacological studies have shown that P. tenuifolia could improve memory impairment caused by scopolamine, stress, glutamate, and Aβ, and promote neuronal proliferation in normal brains (Chung et al, 2002;Lin et al, 2012;Li et al, 2014). Polygalasaponins, such as polygalasaponin B, F, G, and XXXII, are the main components responsible for the action of P. tenuifolia and have been shown to improve cognitive impairment in AD effectively (Ikeya et al, 2004;Xu et al, 2009;Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…("Yuanzhi" in Chinese) is a well-known traditional Chinese medicine (TCM) herb, which was first documented in Shen Nong Ben Cao Jing, and its dried root has for a long time been traditionally used to treat memory loss in Asian countries (Howes and Houghton, 2003;Kwon et al, 2004;Adams et al, 2007). Recent pharmacological studies have shown that P. tenuifolia could improve memory impairment caused by scopolamine, stress, glutamate, and Aβ, and promote neuronal proliferation in normal brains (Chung et al, 2002;Lin et al, 2012;Li et al, 2014). Polygalasaponins, such as polygalasaponin B, F, G, and XXXII, are the main components responsible for the action of P. tenuifolia and have been shown to improve cognitive impairment in AD effectively (Ikeya et al, 2004;Xu et al, 2009;Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…KCHO-1 is a novel mixture comprised of 30% ethanol (EtOH) extracts obtained from nine natural products: Curcuma longa, Salvia miltiorrhiza, Gastrodia elata, Chaenomeles sinensis, Polygala tenuifolia, Paeonia japonica, Glycyrrhiza uralensis, Atractylodes japonica and processed Aconitum carmichaeli. These natural products are well known as traditional medicinal herbs, which are used as alternative therapies in Korea and China, and recent studies have reported the beneficial effects of these herbs (19)(20)(21)(22)(23)(24)(25). In our previous study, it was suggested that KCHO-1 exerted anti-inflammatory effects in BV2 microglia (26).…”
Section: Introductionmentioning
confidence: 97%
“…P. tenuifolia has been used as a cure for both insomnia and amnesia [18]. More recently, it has been prescribed for memory dysfunction and various brain in ammatory diseases [19].…”
mentioning
confidence: 99%